Directed hyper-graphs for RDF documents - Martínez Morales, Amadís Antonio; Vidal, María Esther (Rev. Téc. Fac. Ing. Univ. Zulia, 2010)
Resource Description Framework (RDF) is a W3C proposal to express metadata about resources in the Web. The RDF data model has been formalized using several graph-based representations; each one offers different expressive power and support for the tasks of query answering and semantic reasoning. In this paper, we propose a directed hyper-graph formal model to represent and manage RDF documents efficiently. We have developed algorithms that exploit the properties of the proposed representation, and conducted an experimental study to analyze the space and lime savings of our solution with respect to the labeled directed graph representation. Our study has been performed over synthetic and real-world RDF documents, and we could observe that our approach reduces the space required to store an RDF document and speeds up the task of query answering, overcoming the labeled directed graph representation.